Determination of Antibiotics Resistance Levels in Enterobacteriaceae Isolated from Giresun Coasts - Tamer Akkan; Cengiz Mutlu (Turkish Journal of Agriculture: Food Science and Technology)
In this study the resistance of 200 Enterobacteriaceae isolates recovered from seawater in Giresun Coasts (Black Sea) to 9 different antibiotics was investigated by agar diffusion methods. Antibiotic resistance levels of isolates was determined respectively, Erythromycin (E): 82%, Cefazolin (CZ): 46.50%, Cefotaxime (CTX): 50.50%, Amikacin (AK): 41.50%, Nalidixic acid (NA): 34.50%, Tetracycline (TE): 30.50%, Chloramphenicol (C): 36.50%, Cefuroxime (CXM): 35.50% and Ampicillin (AM): 15.50%. It was found that 2 isolates resistant to all antibiotics, 5 isolates sensitive and 91% of all isolates multiple antibiotic resistance (MAR) index values were higher than 0.2. It was concluded that bacteriological quality in Giresun coastal area could cause public health problems due to the not provided necessary hygiene and sanitation.